Achillodynia – Radiological Imaging of Acute and Chronic Overuse Injuries of the Achilles Tendon - Syha, R.; Springer, F.; Ketelsen, D.; Ipach, I.; Kramer, U.; Horger, M.; Schick, F.; Grosse, U. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
In the past decades the incidence of acute and chronic disorders of the Achilles tendon associated with sport-induced overuse has steadily increased. Besides acute complete or partial ruptures, achillodynia (Achilles tendon pain syndrome), which is often associated with tendon degeneration, represents the most challenging entity regarding clinical diagnostics and therapy. Therefore, the use of imaging techniques to differentiate tendon disorders and even characterize structure alterations is of growing interest. This review article discusses the potential of different imaging techniques with respect to the diagnosis of acute and chronic tendon disorders. In this context, the most commonly used imaging techniques are magnetic resonance imaging (MRI), B-mode ultrasound, and color-coded Doppler ultrasound (US). These modalities allow the detection of acute tendon ruptures and advanced chronic tendon disorders. However, the main disadvantages are still the low capabilities in the detection of early-stage degeneration and difficulties in the assessment of treatment responses during follow-up examinations. Furthermore, differentiation between chronic partial ruptures and degeneration remains challenging. The automatic contour detection and texture analysis may allow a more objective and quantitative interpretation, which might be helpful in the monitoring of tendon diseases during follow-up examinations. Other techniques to quantify tendon-specific MR properties, e. g. based on ultrashort echo time (UTE) sequences, also seem to have great potential with respect to the precise detection of degenerative tendon disorders and their differentiation at a very early stage.Key Points: Citation Format:
Keywords: tendons; MR imaging; ultrasound